A DISTRIBUTION FUNCTION BASED BANDWIDTH SELECTION METHOD FOR KERNEL QUANTILE ESTIMATION - Faucher D.; Rasmussen P.F.; Bobee B. (My University, 2001)
The key problem in nonparametric frequency analysis of flood and droughts is the estimation of the bandwidth parameter which defines the degree of smoothing. Most of the proposed bandwidth estimators have been based on the density function rather than the cumulative distribution function or the quantile that are the primary interest in frequency analysis. We propose a new bandwidth estimator derived from properties of quantile estimators. The estimator builds on work by Altman and Leger (1995). The estimator is compared to the well-known method of least squares cross-validation (LSCV) using synthetic data generated from various parametric distributions used in hydrologic frequency analysis. Simulations suggest that our estimator performs at least as well as, and in many cases better than, the method of LSCV. In particular, the use of the proposed plug-in estimator reduces bias in the estimation as compared to LSCV. When applied to data sets containing observations with identical values, typically the result of rounding or truncation, the LSCV and most other techniques generally underestimates the bandwidth. The proposed technique performs very well in such situations.
Keywords: FLOODS; EXTREME VALUES; STATISTICAL ANALYSIS; FREQUENCY ANALYSIS; TAIL PROBABILITY ESTIMATORS; COMPARATIVE STUDIES